Masculinités variables en temps de crise : deux auteurs-compositeurs-interprètes : fixer le temps, de Dumas. Tacca / La Tribu, 2006 ; Les vendredis, de Stefie Shock. Atlantis, 2006 - Boisclair, Isabelle (Spirale, 2007)
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; arts; culture populaire; discipline; genre; hétérosexisme; masculinité; périodes historiques; québec; ressource en ligne; régions géographiques; systèmes d'oppressions; études littéraires

Lesbian inscriptions in francophone society and culture - Günther, Renate; Michallat, Wendy (Durham Modern Languages, 2007)
This book represents the first comprehensive collection of essays in English dedicated entirely to the study of lesbian inscriptions in francophone society and culture. Spanning the period from the early nineteenth to the twenty-first century, the volume offers a range of interdisciplinary perspectives on ways in which lesbianism has been represented and represented itself, with essays on poetry and the novel, contemporary film and television, photography and architecture. These essays will appeal to students and scholars of gender studies and French literature and culture.
Keywords: afrique; amériques; approches et analyses; arts; belgique; canada; discipline; europe; france; hétérosexisme; identités LGBTQIA2+; régions géographiques; systèmes d'oppressions; études littéraires